Infant formula feeding practices associated with rapid weight gain: A systematic review. Issue 3 (14th April 2018) - Appleton, Jessica; Russell, Catherine Georgina; Laws, Rachel; Fowler, Cathrine; Campbell, Karen; Denney‐Wilson, Elizabeth
Abstract: Excess or rapid weight gain during the first 2 years of life is associated with an increased risk of later childhood and adult overweight and obesity. When compared with breastfed infants, formula fed infants are more likely to experience excess or rapid weight gain, and this increased risk in formula fed infant populations may be due to a number of different mechanisms. These mechanisms include the nutrient composition of the formula and the way formula is prepared and provided to infants. This systematic literature review examines the association between formula feeding practice and excess or rapid weight gain. This review explores these different mechanisms and provides practical recommendations for best practice formula feeding to reduce rapid weight gain. Eighteen studies are included in this review. The findings are complicated by the challenges in study design and accuracy of measurements. Nevertheless, there are some potential recommendations for best practice formula feeding that may reduce excess or rapid weight gain, such as providing formula with lower protein content, not adding cereals into bottles, not putting a baby to bed with a bottle, and not overfeeding formula. Although further well designed studies are required before more firm recommendations can be made.